Improving Rural Livelihood through NERICA Farming: An Inquiry into Najja Sub-county in Central Uganda - Makosa , Dan; Takayanagi, Nagatada (Asian Journal of Agriculture and Rural Development, 2014)
New Rice for Africa (NERICA) was introduced in Uganda to help rural farmers in improving their livelihood in terms of income and food security. Using the livelihood impact analysis technique, this study sought to assess the role of NERICA in improving rural livelihood by (i) understanding the production environment (ii) exploring the marketing opportunities and challenges and (iii) highlighting the changes in livelihood outcomes. The findings indicate that upland varieties are cultivated mainly in lowland areas and rural farmers prefer early maturity attribute to high productivity. Milling places also double as selling points where buyers and sellers meet. Selling milled rice fetches more profits than paddy. The most popular asset purchased from NERICA proceeds is land. The main challenges to production and marketing are inadequate extension service and high transport costs respectively.